Rapid Implementation and Evaluation of Virtual Health Training in a Subspecialty Hospital in British Columbia, in Response to the COVID-19 Pandemic - Hassani, Kasra; McElroy, Theresa; Coop, Melissa; Pellegrin, Joelle; Wu, Wan Ling; Janke, Rita D.; Johnson, L. Kit (Frontiers in Pediatrics, 2021)
Introduction: Adoption of virtual health (VH) solutions in healthcare has been challenging; this changed rapidly after implementation of physical distancing measures due to the COVID-19 pandemic. In response to the pandemic, British Columbia’s Children and Women's sub-specialty hospitals rapidly trained and scaled up support to equip staff and clinicians to utilize VH. Methods: 90-minute live online training workshops and frequently updated online support materials were offered for six weeks. Training was monitored via feedback collected at training sessions and a brief post-training survey. Following training completion, a second survey was circulated to measure utilization outcomes and experiences with VH. Results: 895 participants representing 82% of staff requiring support were trained through 101 sessions; 348 (38.9%) and 272 (30.4%) responses were collected for the monitoring and outcome surveys respectively. Overall, 89% agreed that training was relevant to their needs; participants indicated average 58.1% (SD=26.6) and 60.6% (SD=25.2) increase in knowledge and confidence in VH following training; 90.1% had booked or conducted VH sessions. Increase in confidence was more pronounced in participants with lesser prior exposure to VH, but number of sessions conducted post-training, and percentage of successful sessions were independent of prior exposure. For future training and support, participants suggested subject-tailored trainings, asynchronous trainings, and availability of experienced users. Discussion: Training is key to success of VH implementation. Moving forward, core competencies in VH should be developed to support standardization and allow for evaluation and quality improvement. Incorporation of VH training in continuous professional development and onboarding is also highly recommended.